Validation of the URICA-S in group therapy: associations of stages of change with therapeutic factors and treatment outcome - Mander, Johannes; Vogel, Eva; Blanck, Paul; Bents, Hinrich (The international journal of group psychotherapy, 2018)
Stages of change could be driving forces to activate the realization of therapeutic factors and symptom change. Consequently, the aims of the present study were to investigate whether the stages of change concept is valid in group therapy settings shown by factor analysis, internal consistencies, and criterion validity. A total of 377 patients completed measures of stages of change, symptom change, and therapeutic factors. A confirmatory factor analysis replicated the stages of change factors for group therapy. Related to the criterion validity, stages of change demonstrated only low, non-significant associations with symptom change, but some stages of change were significant predictors of certain therapeutic factors. Further research is needed to explore whether a stronger focus on motivational stages of change could help to intensify the realization of therapeutic factors in group therapy.